Comparative analysis of assertiveness for three built-up zone indexes applied to Colombian cities - Leal Villamil, Julián; Perea Ardila, Mauricio Alejandro; Santa Ramírez, Gabriel Alexis (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The delimitation and Spatio-temporal characterization of built-up or urbanized areas in cities is a fundamental input forterritorial planning. Built-up Zone Indices are used to identify urban areas using remote sensing. The objective of thisstudy was to evaluate the multitemporal assertiveness (1997, 2002, 2007 and 2018) of three Built-up Zone Indices (NDBI,UI and IBI) calculated in Landsat images for three Colombian cities. The images were enhanced through Remote Sensingtechniques and the Built-up Zone Indices were determined by taking into account the parameters established by theircreators. It means that 700 ground truth points (350 for the built-up zone and 350 for the non-built-up zone) were used to establish the multitemporal assertiveness using the Kappa Index. The results show that the index with the best overall multitemporal assertiveness was the NDBI (Kappa = 0.382), which was also the best performing for the largest city (Kappa = 0.566); for the intermediate size city, the most successful index was the UI (Kappa = 0.545). The evaluated indexes had nullKappa values in the city of Espinal; discarding the results obtained in the latter city, the global assertiveness of the indexes can be increased to 0.573. Further research is needed to evaluate in detail the applicability and assertiveness of the indicesin the Colombian context, as well as the adjustments to the optimal value range for each particular city according to its architectural characteristics.